In game role and serve characteristics in Under-14 female volleyball - Fernández-Echeverría, C.; Claver, F.; Gil, A.; Del Villar, F.; Moreno, M. P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The main objective of this study was to analyze the serve characteristics depending on the in-game role, in female formative stages. The sample was comprised of 1229 serves, corresponding to the observation of the 18 teams participating in the Under-14 category Spanish Championship in 2010. The studied variables were: in-game role, serve zone, serve type, striking technique, reception zone, receiver player and serve effectiveness. The results showed a significant association between the in-game role with serve zone, serve type, striking technique and serve effectiveness. However, there is not a association between the in-game with variables that reflect the intention to direct the serve to a specific players or specific area were found.